Identidad, ciudadanía y derecho : del estereotipo al fobotipo - Javier de Lucas (Amnis)
In this paper, I try to offer a contribution on the well-known role of Law as an instrument for the construction and dissemination of stereotypes. Specifically, I will analyze its role in relation to a determinant problem of national identity, the establishment of the dichotomous category of citizenship / foreigner. I will highlight the negative role of immigration law when it comes to building and justifying the progressive and radical difficulty of accessing citizenship. In short, the rejection of that the jurists continue to call « naturalization », an example of legal stereotype that includes, as almost always, its fobotype: what is ours, what is national, is natural. The other is an anomaly. A fobotype to which the Law brings its terrible specificity, its capacity to impose our own view, from the asymmetry of the position of power.